2020
DOI: 10.21203/rs.2.21015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterisation of ampeloviruses associated with mealybug wilt of pineapple disease in Ghana

Abstract: Background: Mealybug wilt of pineapple (MWP) is the most destructive viral disease of pineapple worldwide. The disease is caused by pineapple mealybug wilt-associated virus (PMWaV), a member of the family Closteroviridae and the genus Ampelovirus, and transmitted by mealybugs. Methods: In order to understand the association between closteroviruses and MWP in Ghana, 24 pineapple plant samples showing typical symptoms of MWP were collected during a survey of the Central Region in 2019. Three quantitative reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Both men and women were within the economically active group and had attained primary education (1-6), which is consistent with the 2010 Population and Housing Census results for the chosen districts (GSS, 2010). This result, however, deviates from the norm, where previous studies have found low levels of education among rural folks [30]. Men, however, further continued after primary education, leaving the women behind.…”
Section: Comparison Of the Application Of G+ Tools Versus Conventiona...contrasting
confidence: 82%
“…Both men and women were within the economically active group and had attained primary education (1-6), which is consistent with the 2010 Population and Housing Census results for the chosen districts (GSS, 2010). This result, however, deviates from the norm, where previous studies have found low levels of education among rural folks [30]. Men, however, further continued after primary education, leaving the women behind.…”
Section: Comparison Of the Application Of G+ Tools Versus Conventiona...contrasting
confidence: 82%
“…Employee orientation refers to a process by which a newly inducted employee acquaint with the organization, and it is an opportunity to convey the firm’s vision, mission and values-form the new employee esteems and integrates the employees into the firm’s structure (Asare-Bediako, 2008). Michel (2006) stated that while being engaged in the orientation process, worker development is a key among the most critical construct of the firm’s success.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…It is necessary, therefore, the need for any firm to first identify the training needs of the firm. The need for training should be recognised in accordance with a well-organised procedure looking at the training needs from the firm and employee perspective (Asare-Bediako, 2002). Training Needs Assessment (TNA) ought to be one of the first steps in the training cycle.…”
Section: Training Needs Assessmentmentioning
confidence: 99%